BIOAKUMULASI KADMIUM (Cd) PADA MANTEL, INSANG, dan GINJAL KERANG AIR TAWAR Elongaria orientalis (Lea, 1840) - Selvi Ariyunita; Andhika Puspito Nugroho (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
Cadmium (Cd) is one of non-essensial metals and toxic in low concentration. Cd polution in freshwater ecosystem from the usage of Cd in many industrial activities can interfere biology system of aquatic animals. Evaluation of heavy metals in freshwater ecosystem can be predicted with accumulation of metals in organism. Mussels are aquatic organism that capable to accumulate metals in their body. The purpose of this research were to study pattern of Cd accumulation in body mussels including mantle, gills, and kidneys. Mussels are exposed to Cd via water (20 µgL-1)for 24 days, followed by 12 days of depuration. On day 0, 1, 6, 12, 18, 24 (exposure time) and day 30, 36 (depuration time), mussels were dissected into mantle, gills, and kidneys. Cd bioaccumulation in all organ was determined by using Atomic Absorbance Spectrophotometer (AAS). The result showed that pattern of Cd bioaccumulation attend to increase in all organs within exposure time and attend to decrease within depuration time. The higest level of accumulation being in kidney, followed by gillsand mantle. Keywords: bioaccumulation, cadmium, freshwater mussel